2012
DOI: 10.2174/092986612803217132
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Property and In Vivo Efficacies of Novel Val/Arg-rich Antimicrobial Peptide

Abstract: A novel α-helical antimicrobial peptide G6 rich in Val/Arg residues has been screened previously. In this study, we further evaluated the biochemical stability, interaction with whole bacteria, and in vivo therapeutic or prophylactic role of the peptide in Salmonella typhimurium-infected mice. The results showed that G6 exhibited strong resistance to pH, heat, and salts. But G6 lost the antimicrobial activity when treated with proteolytic enzymes. G6 had no toxicity on mammalian cell. An intraperitoneal model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Therefore, increasing the number of positive charges in an antimicrobial peptide may enhance its antibiotic activity. Arg residue is important for the initial electrostatic attraction of AMPs to the surface of cell membrane . In this study, XPF4 and XPF6 showed remarkable antibacterial activity and only mild hemolytic activity, suggesting that positive charges are critical for the antibiotic activity and selectivity of antimicrobial peptides, which is consistent with the previous studies .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, increasing the number of positive charges in an antimicrobial peptide may enhance its antibiotic activity. Arg residue is important for the initial electrostatic attraction of AMPs to the surface of cell membrane . In this study, XPF4 and XPF6 showed remarkable antibacterial activity and only mild hemolytic activity, suggesting that positive charges are critical for the antibiotic activity and selectivity of antimicrobial peptides, which is consistent with the previous studies .…”
Section: Discussionsupporting
confidence: 92%
“…According to the helical‐wheel projection, Ma et al designed a small combinatorial library of Val/Arg‐rich peptides, and peptide G6 was found to have optimal cell selectivity. G6 has been further demonstrated to reduce peritoneal bacterial counts and increase survival after Salmonella typhimurium infection . Further studies were conducted to assess the effect of net charge and Pro on the activity of Val/Arg‐rich peptides.…”
Section: Classification and Structural Properties Of Antimicrobial Pementioning
confidence: 99%
“…The BODIPY-TR-cadaverine (BC) displacement assay was performed to analyze the LPS binding ability as previously studied ( Ma et al, 2012 ). At the beginning, the LPS-probe solution was formed by 4h incubation of 50μg/ml LPS (derived from Pseudomonas aeruginosa , purchased from Sigma-Aldrich, Shanghai, China) and 5μg/mlBC dye in Tris buffer.…”
Section: Methodsmentioning
confidence: 99%